Desenvolvimento e validação de conteúdo de instrumento de avaliação da atenção nutricional no âmbito da atenção primária à saúde - Almeida, Ana Beatriz Pacito [UNIFESP] (2017)
Introdution: Food and Nutrition (F&N) actions has a central role in healthy promotion and prevention of health problems, and Primary Health Care (PHC) is strategic to the realization of this actions. However, although the Política Nacional de Alimentação e Nutrição (PNAN) establish as the first guideline the organization of Nutritional Care (NC), this continue neglected in PHC and don’t be finded registries in literature about any instrument who propose evaluate it. According to the above, the justification to the realization of this study is based in the necessicity to elaborate and validate the content of an instrument, composed by questions and indicators, able to portray the situation in the Country about the NC provided in the units of PHC and assist the decisions. Objectives: Develop and validate the content of the Instrumento de Avaliação da Organização da Atenção Nutricional (IAAN) whitin the PHC. Methods: The study was approved by the Research Ethics Committee of Universidade Federal de São Paulo on the number of notion 1.661.045. The elaboration of the instrument is based in a extensive literature review to identificate the F&N actions planned in the official guidelines and the possible repercutions for succes of NC. The instrument were reviewed by researchers of area and submitted to an pilot study. Was used the Delphi tecnic to obtain the consensus between the experts nutritionists and, consequently, validation of content of IAAN. The strategies to collect the participants to the validation process included, among others, contact with the profissional concils and researchers associations, and identification of the state coordinators of F&N. Results: The panel of experts was composed by nutritionists who work in different areas of PHC, videlicet: management, department, teaching and research; and all the macro regions of the Country was represented. The content of IAAN was validated in two rounds and its final version got 68 questions and 10 indicators: 1) Acting of nutritionist: graduate, knowledge, relation with the team, workload and work process; 2) Support to the NC actions: infrastructure and permanent education; 3) Intersectoriality; 4) Social control; 5) Food and Nutrition Surveillance; 6) Individual NC; 7) NC for groups; 8) NC at prenatal care; 9) NC at puerperium and breast-feeding; and 10) NC to the child’s health. Conclusion: The process of the validation was fundamental to assegurate the adequation and the representivity of the content of IAAN. The experts’ qualification support the analisys of the instrument and granted the credibility to the validation. The participation of all the macro regions of Brazil made possible the appreciation of the instrument by specialists who worked in different realities. The IAAN turn able the establishment of evaluative process and to represent a method to utilization in researchs. The results obtained with future utilizations could contribute to elaborate a representation of the lived situation in the Country and, therefore, subsidize decisions that promotes progress and improvements of NC.